LIMITATION OF MEANINGFUL PARTICIPATION REQUIREMENTS IN THE INDONESIAN LAW-MAKING PROCESS - Prastyo, Angga (Jurnal Hukum dan Peradilan, 2022)
The Indonesian Constitutional Court through Decision Number 91/PUU-XVIII/2020, in the consideration section, shows how public participation in the formation of laws should be implemented, that is based on formal legal regulations and carried out in a â€œmeaningful participationâ€. Participation is said to be meaningful if the right to be heard, the right to be considered, and the right to be explained or answered to the opinions and inputs given are fulfilled by the legislators. Who the subjects of meaningful participation are, what the limitations of the material or substance of meaningful participation are, where the appropriate space or media for meaningful participation is, and how to consider and answer to meaningful participation is given, will be the problems discussed in this conceptual study. This study needs to be carried out to clarify the limits of meaningful participation so that the concept or theory as the basis can be applied and accommodated in laws and regulations. The main idea of the result of this study is the findings regarding the limits of meaningful participation in the formation of laws, that is the provision of opinions and inputs carried out by parties affected directly or indirectly and have concern to it. In addition, indicators for assessing the substance of participation and receiving opinions and inputs are â€œthe purposeâ€ of the regulation that will be formed. The participation media as well as participation explanations and answers are delivered conventionally and virtually with certain intelligence adjustments to the information technology used.